The Battle Against COVID-19 in Jordan: An Early Overview of the Jordanian Experience - Al-Tammemi, Ala'a B. (Frontiers in Public Health, 2020)
Since the initial spark of the COVID-19 outbreak in December 2019, which was later declared by the World Health Organization (WHO) to be a global pandemic, all affected countries are implementing various preventive and control measures to mitigate the spread of the disease. The newly emerging virus brings with it uncertainty—not only regarding its behavior and transmission dynamics but also regarding the current lack of approved antiviral therapy or vaccines—and this represents a major challenge for decision makers at various levels and sectors. This article aims to provide an early overview of the COVID-19 battle within the Jordanian context, including general reflections and conclusions on the value of collaborative efforts in crises management.